SISTEM PROTEKSI DAN MONITORING KESEIMBANGAN BEBAN TIGA FASA PADA JARINGAN DISTRIBUSI TEGANGAN RENDAH MENGGUNAKAN MIKROKONTROLER BERBASIS IOT - rifdian indrianto; Hartono Hartono; Kustori Kustori; Slamet Hariyadi; Suhanto Suhanto (Politeknik Penerbangan Surabaya, 2023)
Three-phase electrical systems are widely used by industrial consumers because of their large power requirements. The 3-phase system is more economical in the delivery of electrical power than the single-phase system because the conductor used is smaller for the same power. A 3-phase system is said to be balanced if the load used is also balanced between the three R-S-T phases. However, in practice the balance of the three phases is very difficult to achieve because the electrical load of each house or industry is not necessarily identical. As a result of this imbalance between the R-S-T phases can cause damage to electronic equipment that uses 3-phase electricity if used continuously.According to PUIL 2011 the unbalance distribution system includes an unbalanced current between phases with provisions up to a tolerance value of 10%. In a 3 phase electrical distribution system, there will often be load imbalances. This is due to the addition or use of electrical loads that do not pay attention to the imbalance in the system.For this reason, in this study, a tool that uses the PZEM-004T sensor, Wemos D1 mini module, and Android Studio was created which can allow for remote monitoring using electronic devices that have installed applications that have been created. when an error occurs, the